Diet, fruit and vegetable intake, and nutritional status in Fiji: A scoping review - Azupogo, Fusta; Hess, Sonja Y.; Silatolu, Anasaini Moala; Olney, Deanna K. (Wiley, 2026)
Increasing fruit and vegetable (F&V) intake is essential for transitioning toward healthier, more sustainable diets. To design effective intervention programmes to promote F&V intake, it is crucial to understand intake levels and dietary patterns across different demographic groups as well as populations' nutritional status. We conducted a scoping review to summarise scientific evidence on the diet, F&V intake and nutritional status of the Fijian population. In January 2023, we searched PubMed for relevant literature. Studies were eligible if they were published in English since 2012 (for dietary intake and nutritional status) or since 2002 (for F&V) and met predefined inclusion criteria. We identified 163 articles reporting on diet, 47 on F&V intake and 95 on nutritional status. After further review and confirmation that articles met inclusion criteria, data were extracted from 16 articles on diet, 8 on F&V and 13 on nutritional status. The scoping review revealed a shift in Fiji from traditional foods to processed, unhealthy foods, high salt intake and poor dietary diversity. F&V intake was low, with only a quarter of adults and adolescents consuming the recommended daily servings. Approximately 7% of children under-five were stunted, and 8% were overweight. At least 25% of adolescents were overweight or obese, whereas 10% were underweight. Over 30% of adults were obese, and at least 25% were overweight. Overweight/obesity was higher in females and Indigenous Fijians; underweight higher among Indo-Fijian adolescents, especially males. Strengthening population-wide efforts to promote healthy lifestyles and dietary habits is crucial to address these issues.